Symposium 10: Knowledge 2.0 - tensions and challenges for education - Dohn, Nina Bonderup (Proceedings of the International Conference on Networked Learning, 2008)
Communication on the World Wide Web (WWW) is currently evolving from the one-to-many display of information on homepages to the interaction of many participants in the construction of social networks, communities of practice, 'bottom-up' encyclopaedias like Wikipedia (http://www.wikipedia.org/), and collaborative content sharing systems like the one being built in the Connexions project (http://cnx.rice.edu/). This shift in the role of the WWW, and of communication on it, is characterized as the shift from Web 1.0 to Web 2.0 (Downes, 2005; O'Reilly, 2005), and, correspondingly, the technological tools that enable the shift are designated Web 2.0-technologies. Likewise, the new communication practices can be termed Web 2.0-practices. Closely linked to the development of such Web 2.0 communication practices, requisite to it as well as supported by it, is a change of attitude towards issues such as authorship, copyright, knowledge production, and expertise. In many educational programmes, Web 2.0 technologies and practices are being introduced into the teaching and learning activities. The reasons for doing so can be manifold: One argument would be that employing in the service of learning some of the communication practices that young people are already using will ease the transition into the learning practices of the university, both in respect of the motivation of the students and of the skills required of them. Another argument is that the centrality of participation, production, and dialogue in Web 2.0-practices make them ideal as elements in programmes focusing on the learner's active engagement as a prerequisite for learning. Still a third reason is that many of the possible future jobs of the students will require competence in the use of Web 2.0, and therefore a new task of educational programmes arguably is to support the acquisition of such competences along with other subject-related competences. However, introducing Web 2.0-practices into learning activities in an educational setting in many cases leads to tensions in practice. The aim of this paper is to discuss these tensions, arguing that they are the result of conceptual tensions in the teleology and epistemology implicit in Web 2.0-practices on the one hand and the educational system on the other: Implicit in Web 2.0-practices is a conception of 'knowledge' as, on the one side, process and activity, i.e. as use, evaluation, transformation and reuse of material, and, on the other, the product side, as a distributed attribute of a whole system (such as Wikipedia) or community of practice (such as the community of practice of Wikipedia contributors). Similarly, learning is viewed along the lines of Wenger as participation. In contrast, 'knowledge' within the educational system is traditionally viewed as a state possessed by the individual, and learning as the acquisition of this state, be this achieved through behaviouristic 'knowledge transfer' from teacher to student, or through Piagetian construction or Vygotskian internalization of socially mediated knowledge. The tensions created when these different conceptions are brought into play in practice through the integration of Web 2.0 in teaching and learning result in a number of questions for the educational programmes. Among these are: Is student competence in evaluating the quality of accessible material and putting such material to use in new situations more important than individual production of material? Should student participation be evaluated for quality or is participation a goal in itself for Web 2.0 learning activities? If the former, which type of criteria should quality be evaluated in terms of - educational criteria or criteria internal to the Web 2.0-practices involved? If the latter, are there no minimal requirements on the content of what the participation is about; as regards the subject matter and what more specifically is said/written about this subject matter? If not, how can students trust themselves (and the educational programme) to use subject matter produced in a Web 2.0-supported course in their further studies and in their working lives?